Implementation of Team Assisted Individualization (TAI) Learning Model to Improve Student’s Activeness and Learning Outcomes on Reaction Rate Materials - Febrian Solikhin; Nurul Nikmah; Akmal Chairunisa (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Abstract: Implementation of Team Assisted Individualization (TAI) Learning Model to Improve Student’s Activeness and Learning Outcomes on Reaction Rate Materials. Objectives: The aims of this study to improve student’s activeness in learning process and student’s learning outcomes by applying the Team Assisted Individualized (TAI) type of Cooperative learning model. Methods: This research is classroom action research (CAR). It use 2 learning cycles consisting of planning, implementation, observation, and reflection. The subjects of this study were students of class XI Science 1, MAN 1 Bengkulu City which consisted of 12 male students and 23 female students. The problem in this class is the lack of student participation in the learning process. This causes a decrease in learning outcomes in each material. Findings: Increased student's activeness from 43.80% in the first cycle to 77.14% in the second cycle. While the percentage of mastery learning outcomes increased from 22.85% in the first cycle to 80.0% in the second cycle. Conclusion: These results state that the TAI type of cooperative learning model can increase the percentage of learning activeness and mastery of learning outcomes.